1998
DOI: 10.1076/apab.106.5.384.4362
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Electroencephalographic Changes Due To Middle Cerebral Artery Occlusion By Endothelin 1 In Conscious Rats

Abstract: The powerful vasoconstrictor peptide endothelin-1 (ET1) has been shown to reduce local cerebral blood flow in brain areas supplied by the middle cerebral artery (MCA) to a pathologically low level upon intracerebral injection adjacent to the MCA. This reduction manifests itself as an ischemic infarct, that is fully developed within 3 days after ET1 injection. The aim of the present study is to examine the effect of ET1 on electroencephalographic (EEG) activity. ET1 was microinjected unilaterally at a dose of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
0
17
1
Order By: Relevance
“…A model of reversible focal ischemia using ET1 was used as previously described (Moyanova et al, 1998;Biernaskie et al, 2001).…”
Section: Animal Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…A model of reversible focal ischemia using ET1 was used as previously described (Moyanova et al, 1998;Biernaskie et al, 2001).…”
Section: Animal Modelmentioning
confidence: 99%
“…More recently, stereotaxic application of ET1 near the MCA (Robinson et al, 1990;Sharkey et al, 1993Sharkey et al, , 1994Sharkey and Butcher, 1995;Macrae et al, 1993;Moyanova et al, 1998;Biernaskie et al, 2001;Bogaert et al, 2000;Callaway et al, 2000) has been shown to produce a profound reduction of blood flow that leads to cerebral ischemic injury within the MCA territory. Several well-established models of ET1-induced MCA occlusion have been demonstrated (Robinson et al, 1990;Sharkey et al, 1993Sharkey et al, , 1994Sharkey and Butcher, 1995;Macrae et al, 1993;Moyanova et al, 1998;Biernaskie et al, 2001;Bogaert et al, 2000;Callaway et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, ET1 was used as a tool to produce severe and sustained, but ultimately reversible unilateral MCA occlusion in order to provide an animal model of focal cerebral ischemia with reperfusion [14][15][16][17][18][19][20][21][22][23][24][25]. The quantitative EEG and the neurological examination both showed a substantial effect of ET1.…”
Section: Discussionmentioning
confidence: 84%
“…In this model, occlusion of the middle cerebral artery (MCAO) was induced in rats via intracerebral microinjection of Endothelin-1 (ET1) -the so-called EMCAO model. While some consequences of EMCAO on blood perfusion, behavior and histopathology have been explored in certain extent [14][15][16][17][18][19][20][21], the corresponding changes of bioelectrical activity are less investigated [22][23][24][25]. The brain electrical signals are in the list of mandatory outcome measures according to the recommendations from the first Stroke Academic Industry Roundtable meeting for the preclinical evaluation of neuroprotective and recovery enhancing drugs [26].…”
Section: Introductionmentioning
confidence: 99%